Pre-Eclampsia Biomarkers for Women With Type 1 Diabetes Mellitus: A Comprehensive Review of Recent Literature - Freimane, Katrina Z.; Kerrigan, Lauren; Eastwood, Kelly-Ann; Watson, Chris J. (Frontiers in Bioengineering and Biotechnology, 2022)
Background: Pre-eclampsia is a serious consideration for women with type 1 diabetes mellitus (T1DM) planning pregnancy. Risk stratification strategies, such as biomarkers measured in first trimester of pregnancy, could help identify high-risk women. The literature on T1DM-specific pre-eclampsia biomarkers is expanding. We aimed to provide a narrative review of recently published evidence to identify the most promising biomarker candidates that could be targeted for clinical implementation in existing PE models. Methods: A search using MeSH terms was carried out of Medline, EMBASE, Maternity and Infant Care, Web of Science and Scopus for relevant papers published since 2015 inclusive and in English language. The time limit was applied from the publishing of the preceding systematic review in this field. Included studies had pre-eclampsia as a primary outcome, measured one or more serum, plasma or urine biomarkers at any time during pregnancy and had a distinct group of women with T1DM who developed pre-eclampsia. Studies with pre-eclampsia as a composite outcome were not considered. No restrictions on study types were applied. A narrative synthesis approach was adopted for analysis. Results: A total of 510 records were screened yielding 18 eligible studies relating to 32 different biomarkers. Higher first trimester levels of HbA1c and urinary albumin were associated with increased risk of pre-eclampsia development in women with T1DM. Urinary neutrophil gelatinase associated lipocalin and adipokines were novel biomarkers showing moderate predictive ability before 15 gestational weeks. Two T1DM-specific pre-eclampsia prediction models were proposed, measuring adipokines or urinary neutrophil gelatinase associated lipocalin together with easily attainable maternal clinical characteristics. Contradicting previous literature, pre-eclampsia risk in women with T1DM was correlated with Vitamin D levels and atherogenic lipid profile in context of haptoglobin phenotype 2-2. Pregnancy associated plasma protein-A and soluble Endoglin did not predict pre-eclampsia in women with T1DM, and soluble Fms-like tyrosine kinase 1 only predicted pre-eclampsia from third trimester. Conclusions: Maternally derived biomarkers reflecting glycaemic control, insulin resistance and renal dysfunction performed better as PE predictors among women with T1DM than those derived from placenta. These biomarkers could be trialled in current PE prediction algorithms to tailor them for women with T1DM.